How Do Users Perceive Nudges Against Online Misinformation? A Repertory-Grid Study* - Konstantinou, Loukas; Karapanos, Evangelos (My University, 2025)
The importance of behaviorally informed interventions against misinformation is increasingly acknowledged, and the concept of nudging has received attention as a promising approach to promoting conscious decision-making when confronted with online misinformation. Nudges, however, may not always produce the desired behaviors; they may lead to side effects, and even backfire. With nudges most often being studied behaviorally, this article argues for the importance of inquiring into users’ perceptions before deploying nudges in the field. We employ a semi-structured interviewing technique, the Repertory-Grid Technique, to inquire into how end-users, like citizens, journalists and policymakers, perceive six concepts of technology-mediated nudging designed to counter online misinformation. The study identifies nine construct categories, such as respectfulness, proactivity, and simplicity, which participants employed to differentiate among and evaluate the nudges. By considering these constructs during nudge design, choice architects can mitigate risks regarding their acceptance and sustained effectiveness. This study contributes to a growing body of literature on the factors that shape nudge failure.
Keywords: nudging; Online misinformation; perception; repertory-grid